Isolated tubercular dacryoadenitis in a non-immunocompromised healthy adult - Ajax Jossy; N Kaviyapriya; Nirupama Kasturi; Sree J Rekha (Indian Journal of Pathology and Microbiology)
A middle-aged woman presented with a slowly enlarging mass in the right superotemporal orbit and ptosis. The patient had an elevated erythrocyte sedimentation rate, and incisional biopsy showed granulomatous inflammation with Langhan's giant cells suggestive of a tubercular etiology. Tuberculin skin test was negative. The patient responded well to anti-tuberculous therapy. Tubercular dacryoadenitis is a rare presentation of a lacrimal gland mass.